Gender, Anxiety, and Depression in Connection to Hikikomori - Danang Nur Adiwibawa; Ayu Anulus; Fahriana Azmi; Chee Kok Yoon; Trisakti Halimah Delimasari (Media Kesehatan Masyarakat Indonesia, 2025)
Hikikomori is a mental health condition characterized by social withdrawal, causing distress for both the affected individuals and those around them. While factors such as gender, anxiety, and depression have been linked to hikikomori, research on this condition in Indonesia remains limited. This study investigated the association between gender, depression, and anxiety with the risk of hikikomori in West Lombok, Indonesia.  A cross-sectional study was conducted at Hospital X in West Lombok, Indonesia, involving 60 patients with depression attending the Mental Health Polyclinic. The respondent ages ranged from 20 to 79 years. Data on gender, depression, anxiety, and hikikomori were collected using self-rated questionnaires and analysed with the Chi-square test.  The results showed that patients with moderate-severe anxiety had a fivefold increased risk of hikikomori (OR=5.00; 95% CI=1.42-17.57; p=0.009). Female patients were 2.5 times more likely to be at risk compared with male patients, while those with moderate-severe depression had a 2.83 times higher risk. However, this association was not statistically significant.  The study concluded that anxiety is a significant risk factor for hikikomori, whereas the association between gender and depression requires further investigation. Understanding these relationships is crucial for developing targeted mental health interventions and improving support for individuals at risk of hikikomori in Indonesia.